2016
DOI: 10.1172/jci.insight.85935
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 marks dysfunctional regulatory T cells in malignant gliomas

Abstract: Immunotherapies targeting the immune checkpoint receptor programmed cell death protein 1 (PD-1) have shown remarkable efficacy in treating cancer. CD4+CD25hiFoxP3+ Tregs are critical regulators of immune responses in autoimmunity and malignancies, but the functional status of human Tregs expressing PD-1 remains unclear. We examined functional and molecular features of PD-1hi Tregs in healthy subjects and patients with glioblastoma multiforme (GBM), combining functional assays, RNA sequencing, and cytometry by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(183 citation statements)
references
References 66 publications
8
168
2
Order By: Relevance
“…We found that the cellular subsets that represented the tumor tissue exhibited an exhausted and immunosuppressive phenotype, as evidenced by the enhanced expression of multiple exhaustion markers (PD-1, CD152, and Lag-3), accumulation of IL-10-expressing immunosuppressive Treg and TAM subsets, and low expression of inflammatory cytokines (TNFα, IFNγ, and granzyme B) by tumor-infiltrating T and NK cells. The role of exhaustion markers (particularly PD-1) on Treg function remains controversial, as it was demonstrated in malignant gliomas that PD-1 hi Treg was dysfunctional and produced IFNγ (26). Others have described that PD-1 expression is correlated with more suppressive Treg phenotypes in chronic viral infection (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the cellular subsets that represented the tumor tissue exhibited an exhausted and immunosuppressive phenotype, as evidenced by the enhanced expression of multiple exhaustion markers (PD-1, CD152, and Lag-3), accumulation of IL-10-expressing immunosuppressive Treg and TAM subsets, and low expression of inflammatory cytokines (TNFα, IFNγ, and granzyme B) by tumor-infiltrating T and NK cells. The role of exhaustion markers (particularly PD-1) on Treg function remains controversial, as it was demonstrated in malignant gliomas that PD-1 hi Treg was dysfunctional and produced IFNγ (26). Others have described that PD-1 expression is correlated with more suppressive Treg phenotypes in chronic viral infection (27).…”
Section: Discussionmentioning
confidence: 99%
“…First, we focused on Tregs, given their well-established correlation with poor prognosis in various cancers, including HCC (23)(24)(25). Recent studies have also demonstrated the expression of exhaustion markers on Tregs, in particular PD-1, and their effect on Treg function (26,27). We then examined whether the Tregs expressed different immune exhaustion markers between the TIL, NIL, and PBMC groups.…”
Section: Lag-3mentioning
confidence: 99%
“…PD-1 hi Tregs in the TME in glioma patients have been found to be exhausted, yet capable of generating proinflammatory cytokines, such as IFN-γ (35). This suggests that one mechanism for the impaired function of anti-PD-1 antibody therapy is the presence of PD-1-expressing Tregs that can (a) bind antibody widely by subtype.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the high expression of PD1 on CD8 + and CD4 + T cells, PD-L1 is expressed on 50—60% of HNSCC tumours[84,88]. While overexpression of PD-L1 inhibits tumour-directed T-cell cytotoxicity and permits immune evasion and tumour growth, prognostic significance of PD-L1 expression by tumours has been variable, correlating with worse outcomes in some cases [8992] and improved outcome in others [93]. Regardless, blockade with an anti-PD-L1 mAb promotes immune-mediated tumour rejection and destruction of tumours [94].…”
Section: Mechanisms Of Immune Escape In Hnscc and Implications Formentioning
confidence: 99%